The Anti-Inflammatory Drug Aspirin Does Not Protect Against Chemotherapy-Induced Memory Impairment by Paclitaxel in Mice - Chang, Aeson; Chung, Ni-Chun; Lawther, Adam J.; Ziegler, Alexandra I.; Shackleford, David M.; Sloan, Erica K.; Walker, Adam K. (Frontiers in Oncology, 2020)
Inflammation has been proposed to play a causal role in chemobrain which—if true—would represent an opportunity to repurpose existing anti-inflammatory drugs for the prevention and treatment of chemobrain. Here, we show that the chemoagent paclitaxel induces memory impairment and anhedonia in mice within 24 h of treatment cessation, but inflammation is not present until 2 weeks after treatment. We find no evidence of brain inflammation as measured by cytokine analysis at any time point. Furthermore, treating with aspirin to block inflammation did not affect paclitaxel-induced memory impairment. These findings suggest that inflammation may not be responsible for memory impairment induced by paclitaxel. These results contrast with recent findings of a causal role for inflammation in cancer-induced memory deficits in mice that were prevented by treatment with oral aspirin, suggesting that cognitive impairment in cancer patients undergoing treatment may arise from multiple convergent mechanisms.